Neonatal Scurvy- A Rare Case Report - Chowdhury, Kona; Rahman, Md Hamidur; Begum, Mahmuda; Akter, Amina (Bangladesh Journal of Child Health, 2024)
Scurvy, a disease of vitamin C deficiency, is now considered as a rare disease in paediatric population. The human body is dependent on the external supply of vitamin C. The newborn infant receives this from breast milk. Therefore, infantile scurvy is generally observed only in infants over the age of three months. The occurrence of scurvy before that age is extremely rare. We described a case of neonatal scurvy in a 28 days old boy who was on parenteral nutrition for initial 10 days of age due to neonatal sepsis with perinatal asphyxia. BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 92-94